EVOLUTION OF AGRITOURISTIC ACTIVITY IN POLAND AND TYPOLOGY OF RURAL TOURISM FARMS - Zawadka, Jan (Acta Scientiarum Polonorum. Oeconomia, 2010)
The study presents agritourism on a background of contemporary tendencies of tourism development. The author presented the beginning and stages of agritourism development in Poland and marked the features characteristic for all stages. The study presents different types of agritouristic holdings and takes into account especially their connection with agricultural activity. Moreover, the author emphasized directions of agritouristic activity in Poland.